Upgrading of lobby and gallery of Perak Tourist Information Centre, for Majlis Bandaraya Ipoh at Jalan Bandar, 3000 Ipoh, Perak / Nursyahira Shafei - Shafei, Nursyahira (Faculty of Architecture, Planning and Surveying, 2011)
This project is about tourist information centre which is upgrading lobby and gallery of Perak Tourist Information Centre for Majlis Bandaraya Ipoh at Jalan Bandar, 3000 Ipoh, Perak. The reason why this project was chosen because the upgrading works on1st floor and 2nd floor of the building is in a progress. But the lobby and gallery is not upgrade yet. The aim of this project is to redesign the lobby and the gallery tourist information centre to have a better space planning. This is to achieve the design objectives of the project. From the research and observation conducted on the activity and site, all of this will be gathered as a guideline to redesign the existing space. The project that was chosen is in a centre of Ipoh which is at Jalan Bandar near Ipoh Padang. The design objectives to achieve in this project are to create a proper flow of lobby & gallery. This centre is a place to attract tourists to get more information about what happen in a state.